Radiation-induced production of PAR-1 and TGF-beta 1 mRNA in lung of C57Bl6 and C3H murine strains and influence of pharmacoprophylaxis by ACE inhibitors - Matej, Radoslav; Housa, Daniel; Poucková, Pavla; Zadinová, Marie; Olejár, Tomás (Pathology, research and practice, 2007)
Transforming growth factor beta 1 (TGF-beta1) plays an important role in the development of radiation- and drug-induced organ diseases. Proteinases-activated receptor 1 (PAR-1) is involved in many pathophysiologic processes after its activation by serine proteases. The aim of the present study was to determine messenger RNA (mRNA) production of TGF-beta1 and PAR-1 in the lungs after local irradiation. Mice of C57BL/6 and C3H/J strains with different susceptibility to fibrosis development were exposed to a of 15Gy. Non-irradiated mice of both strains were used as negative controls. Control (irradiated) and irradiated angiotensin-converting enzyme (ACE) inhibitor-treated animals were examined simultaneously. The ACE inhibitor group was given butylaminiperindopril for 9 days after irradiation (15Gy) at a daily dose of 0.1 or 0.2mg/kg per rectum. On day 9, all mice were sacrificed, and the production of mRNA TGF-beta1 and PAR-1 in lung tissue was determined semiquantitatively using reverse transcriptase polymerase chain reaction, and immunohistochemical analysis of PAR-1 expression in pulmonary tissue was performed. In the fibrosing murine strain C57Bl/6, there was an increase in the mRNA TGF-beta1 and PAR-1 levels in lungs 9 days after irradiation as compared with non-irradiated controls and non-fibrosing murine strain C3H/J. In butylaminiperindopril-treated mice, a decrease in transcript of TGF-beta1 and PAR-1 was observed. Thus, PAR-1 is involved in radiation-induced lung fibrosis in correlation with TGF-beta1 production. Administration of ACEI influences PAR-1 and TGF-beta1 expression.
Keywords: Angiotensin-Converting Enzyme Inhibitors; messenger RNA; Gamma Rays; experimentální radiační poranění; Immunoenzyme Techniques; perindopril; radioprotektivní látky; Female; Radiation-Protective Agents; polymerázová řetězová reakce s reverzní transkripcí; Lung; inhibitory ACE; myši inbrední C3H; Mice, Inbred C3H; záření gama; Reverse Transcriptase Polymerase Chain Reaction; zvířata; myši; plíce; myši inbrední C57BL; Mice; Perindopril; imunoenzymatické techniky; RNA, Messenger; Radiation Injuries, Experimental; ženské pohlaví; Pulmonary Fibrosis; transformující růstový faktor beta; Mice, Inbred C57BL; Transforming Growth Factor beta; receptor PAR-1; Animals; plicní fibróza; Receptor, PAR-1